DIAGNOSA KEMARJINALAN KELEMBAGAAN LOKAL UNTUK MENUNJANG PEREKONOMIAN RAKYAT DI PEDESAAN - ROOSGANDHA ELIZABETH (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2008)
Failure of development in rural mirror marginalitically of local institute and brittle, which candepict influence affect crisis to national economy. Rural development program which less liftsovereignty (politics) socialism economic activity, uncared and also its rural resource interest factorrepresent its uncared evidence traditional institute and structure, and the rural economics too; sothat progressively of brittle. All planner and organizer of development assessed less comprehend itsimportant role of rural local institute to development of rural economics and agricultural sector insustaining national economy. If this condition anticipated, efficacy transformation of local instituteto economics of rural society includes; cover culture social typically can be existed, what supportedpowered of human resource and leadership factor as actor of progress activator.